Pengaruh Financial Disstress, Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Opini Audit Sebagai Variabel Moderasi - Azriel Naufal Firdaus; Sofyan Helmi Purba (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of financial distress and company size on firm value using audit opinion as a moderating variable. The research method used in this study is quantitative. The data used in this study is secondary data obtained from the Indonesia Stock Exchange website for the period 2021 to 2024. The sampling method in this study is purposive sampling using several criteria appropriate to the needs of this study. The sample in this study is 11 property and real estate companies, resulting in a total of 44 observations. Hypothesis testing was conducted using eviews 12. The results of the data analysis conducted in this study partially indicate that financial distress has a negative effect on firm value, and company size has no effect on firm value. The results of the data analysis conducted in this study indicate that simultaneously, financial distress and company size have a significant positive effect on firm value. Meanwhile, the results of the moderating regression analysis (MRA) test in this study indicate that audit opinion cannot moderate the relationship between financial distress and company value, and audit opinion cannot moderate the relationship between company size and company value